2017- CSA Monitoring: Lawra-Jirapa Climate-Smart Village (Ghana) - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Jarvis, Andrew; Ouédraogo, Mathieu; Zougmoré, Robert B.; Nyuor, Anslem Bawayelaazaa; Saaka Buah, Samuel (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
his dataset contains the files produced in the pilot implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Lawra-Jirapa Climate Smart Village (Uganda) in October 2017. This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Hoima Climate Smart Village (Uganda) in October 2018. This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: